The Effect of Peer Assisted Learning Strategy toward Students’ Writing at English Education Program of Muhammadiyah University of Bengkulu - Ade Patriona (Teaching English and Language Learning English Journal, 2022)
This study aims to determine the differences effect before and after use Peer Assisted Learning (PAL) Strategy in teaching writing (in the form of pre-test and post-test scores) on 20 students at English students in Muhammadiyah University of Bengkulu, by providing treatment using the Peer Assisted Learning (PAL) Strategy. This type of research is Quasi Experiment. The population is students of Muhammdiyah University of Bengkulu in the academic year 2020/2021 with 62 students each class is 26 students A class and 36 students in B class. From this population, 20 students were taken as samples in A class 10 students as a control class and 10 students as experimental class. Research data were collected through writing tests and documentation. The results showed a significant change in the experimental class with an average value of 76.67 while in the control class an average value of 69,89 The post-test results show that the Peer Assisted Learning (PAL) Strategy can improve students' writing skills. Thus, the Peer Assisted Learning (PAL) Strategy can be one of effective strategy to increase students writing skills. Keywords: Peer Assisted Learning, (PAL) Strategy, Writing Narrative Texts